Reestructuración comercial administrativa de la empresa Clínica Santa Catalina S.A.S (2018)
The study developed, consisted on the administrative commercial restructuring of Santa Catalina SAS Clinical, which hires surgical rooms for specialized medical equipment, for low complexity surgical procedures which doesn't require intensive care unit afterwards. It started with a diagnosis of the medical sector, identifying the organization and parameters for the execution of the next chapters. Subsequently, it was developed a market research, using prime recollection tools as interviews and polls with the clinic personnel, likewise, a competitive profile matrix and a Marketing mix plan was elaborated, which will improve and enhance the competitive level and the incomes of the organization. On the administrative study it is proposed a new strategic plan for the company, projected to 5 years, a new organizational design was developed (organigram), new function manuals were written and a salary study was made. Additionally, a recruitment, selection, personal development and capacitation model was designed.